THE IMPACT OF REWARD AND PUNISHMENT ON THE MOTIVATION FOR ELEMENTARY SCHOOL STUDENTS - Heru Purnomo; haflah, khairuna (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
The study was done to identify the impact of reward and punishment for the study of the fourth grade student of the country plakind 2 mlati degrades at the physical education learning game (a sphere). Both methods are expected to achieve the best and optimal purpose of learning so that it can build a child's early activation to create an active child. The type of research that is done is field research using quantitative methods. The data-collection technique used is in-depth observation and documentation, this research places more emphasis on observation and requires keen instinct. Recognition and punishment are two contradictory words, but two related things. Rewards and punishments are also employed in order to motivate a child to continue growing so that not only in material but also activity can support child activity. Research indicates that reward and punishment provided a favorable effect on the study of the fourth year students of the country's 4th grade plaves